37-Day microgravity exposure in 16-Week female C57BL/6J mice is associated with bone loss specific to weight-bearing skeletal sites. - Rukmani Cahill; Elizabeth A Blaber; Cassandra M Juran; Margareth Cheng-Campbell; Joshua S Alwood; Yasaman Shirazi-Fard; Eduardo A C Almeida (PLoS ONE)
Exposure to weightlessness in microgravity and elevated space radiation are associated with rapid bone loss in mammals, but questions remain about their mechanisms of action and relative importance. In this study, we tested the hypothesis that bone loss during spaceflight in Low Earth Orbit is primarily associated with site-specific microgravity unloading of weight-bearing sites in the skeleton. Microcomputed tomography and histological analyses of bones from mice space flown on ISS for 37 days in the NASA Rodent Research-1 experiment show significant site-specific cancellous and cortical bone loss occurring in the femur, but not in L2 vertebrae. The lack of bone degenerative effects in the spine in combination with same-animal paired losses in the femur suggests that space radiation levels in Low Earth Orbit or other systemic stresses are not likely to significantly contribute to the observed bone loss. Remarkably, spaceflight is also associated with accelerated progression of femoral head endochondral ossification. This suggests the microgravity environment promotes premature progression of secondary ossification during late stages of skeletal maturation at 21 weeks. Furthermore, mice housed in the NASA ISS Rodent Habitat during 1g ground controls maintained or gained bone relative to mice housed in standard vivarium cages that showed significant bone mass declines. These findings suggest that housing in the Rodent Habitat with greater topological enrichment from 3D wire-mesh surfaces may promote increased mechanical loading of weight-bearing bones and maintenance of bone mass. In summary, our results indicate that in female mice approaching skeletal maturity, mechanical unloading of weight-bearing sites is the major cause of bone loss in microgravity, while sites loaded predominantly by muscle activity, such as the spine, appear unaffected. Additionally, we identified early-onset of femoral head epiphyseal plate secondary ossification as a novel spaceflight skeletal unloading effect that may lead to premature long bone growth arrest in microgravity.